AlGaAs/GaAs asymmetric‐waveguide, short cavity laser diode design with a bulk active layer near the p‐cladding for high pulsed power emission. Issue 4 (30th March 2021) - Avrutin, Eugene A.; Ryvkin, Boris S.; Kostamovaara, Juha T.
Abstract: It is shown theoretically that a GaAs/AlGaAs laser diode design using an asymmetric waveguide structure and a bulk active layer (AL), located close to the p‐cladding, can provide high output power in a single, broad transverse mode for short‐wavelength (<0.9 μm, matching the spectral range of high efficiency of silicon photodetectors) pulsed emission in the nanosecond pulse duration region, typically <<100 ns. The dependences of the laser performance on the thickness of the AL and the cavity length are analysed. It is shown that the relatively thick bulk AL allows the of short cavity lengths (<1 mm), for achieving high pulsed power while maintaining a relatively low series resistance and a narrow far field.